Regime de políticas públicas no Brasil: o processo decisório para a adoção do Programa Bolsa Família - Rezende, Camila Silva (2016)
The conditional cash transfer programs are social policies that focus on vulnerable populations in order to assure income distribution and access to social services like public health and education. Such strategies against poverty have been adopted in several countries and they have found special receptiveness in Latin America, where they first originated as innovations in Brazil and Mexico, from which they have diffused. In Brazil the conditional cash transfer programs emerged from municipalities and they were later bottom-up incorporated to the national social aid system as Bolsa Escola and later as Bolsa Família. As the policy making isn’t neutral nor objective, the context involved in it deeply influences its results, making the understanding of the influencing factors a central issue. In this work the context of the Bolsa Família’s decision making process is analyzed using the policy regimes concept and identifying actors, ideas and institutions. The analysis of documents from the Conselho Nacional de Assistência Social and the Comissão de Seguridade Social e Família of the Chamber of Deputies, speeches of congressmen about the issue and newspaper articles about Bolsa Família in 2003 indicates that the previous existence of similar policies in municipalities and states across the country and the adoption of the program by an interim measure, with the decision making concentrated in the Presidency of Brazil, detracted its acceptance, but the policy regime was receptive to the CCTs, producing a negative choice and not changing the status quo.